Effect of the Ceramic Burning Temperature on the Characteristics of the Emission Spectrum (LIBS) of Al and Transmittance (FTIR) of Al-O on Ceramic Body of BL-1 Type - Wendri, Nyoman; Krisandi, Aprilion; Irawan, I Gusti Putu Yoyok (BULETIN FISIKA, 2020)
Aluminum (Al) contained in materials such as clay, kaolin is one of the elements that play an important role in the ceramic body. Al binds to other atoms like Si (quartz) to form a ceramic frame that is strong and not easily cracked. In addition, the bond with the group -OH plays an important role in relation to the ability of ceramics to absorb water. In this study, BL-1 type ceramic samples have been made with five variations of the burning temperature between 800-1000 o C. To determine changes in the Al atomic content of ceramic samples were characterized by LIBS and FTIR spectrophotometers. The results of LIBS characterization of all samples showed two bands with peaks at wavelengths of 394.4 nm (Al-I) and 396.6 nm (Al-II) which are the characteristic peaks of Al atoms. The peaks with the highest intensity of Al-I and Al-II were resulted by samples that were burned at 900 o C. Meanwhile, the results of FTIR characterization have shown a spectrum with bands at wavenumbers between 1030-1060 and 1150 cm -1 which are characteristic bands of stretching vibrations from Al-O. The peak of the band in the wavenumber between 1030-1060 cm -1 shifts towards a larger wavenumber with increasing the burning temperature.